The Role of Zoosemiotic Inquiry in Shared Environments: Interlinking Nature and Culture - Mäekivi Nelly (Cultural Science)
Environmental humanities study how human worldviews and culture affect the rest of the nature and our interactions with it. Zoosemiotics provides a unique perspective on human-alloanimal communication and analyzes communication dynamics to address the complexities and competing goals in shared environments, recognizing that human interpretations of alloanimal behavior are often anthropocentric. Understanding alloanimal agency and subjective experiences helps create more respectful and harmonious shared environments. By offering case-studies from zoological gardens and species conservation we hope to guide conservation endeavors, environmental conflict resolution, and more sustainable relationships in the Anthropocene. In examining these shared environments, we also indicate how cultural perceptions and practices influence interspecies interactions, thus emphasizing the interconnectedness of culture and ecology.